Estudio florístico en el área de la comunidad indígena de Nuevo San Juan Parangaricutiro, Michoacán, México - Medina García, Consuelo; Guevara-Féfer, Fernando; Martínez Rodríguez, Marco Antonio; Silva-Sáenz, Patricia; Chávez-Carbajal, Ma. Alma; García Ruiz, Ignacio (Instituto de Ecología, A.C., 2000)
The inventory of the vascular flora in the area of comunidad indígena de Nuevo San Juan Parangaricutiro produced the following results: 108 families with 307 genera, 716 species and 16 infraespecific taxa. From this total 52 species belong to pteridophytes, 16 to gymnosperms, 120 to monocotyledons and 544 to dicotyledons. The best represented families, in terms of species number are: Compositae (135), Leguminosae (58), Gramineae (57), Labiatae (26), Solanaceae (21), Orchidaceae (20), and Polypodiaceae (18). 60.7% of the species are herbaceous (either perennial or annual plants); 19.1% are shrubs, 10.0% trees, 4.2% lianas, 3.3% are epiphytic plants, 1.8% are parasites, “saprophytes” amount to 0.5% and aquatics 0.4%.